Metodologia de projeto para arranjo estrututal de carroceria de ônibus através de sistemas modulares - Viero, Carlos Frederico (2013)
The need to rapidly deliver differentiated products to the market and simplify as much a possible the design and manufacturing process makes the study of modularity grow sharply in the current scenario of the manufacturing companies. This paper realizes the implementation of modular concepts in an adapted form, in developing a project structural arrangement for intercity bus body. The proposed use of some concepts of modular product design, to the development of a structural arrangement of bus body, aims to simplify the way you design this structural arrangement, build it and ride it. These modular concepts have been applied in an Erechim s bus company Comil Bus S/A. The main concepts of modular design of the product, which have been shown in the theoretical framework, are structured in the form of a methodology which is divided into two phases. The synthesis or elementarization components phase and behavior phase analysis of these components. To demonstrate the application of this methodology was used based subsystem. Base is subsystem of the structural arrangement system of the bus. Initially it is synthesized and later his behavior is analyzed as a function of external agent chassis